UNIVERSITY STUDENT PERCEIVED EMPLOYABILITY: BIBLIOMETRIC ANALYSIS - Rosse Mayada Pratiwi; Shafa Kirana Dewani; Dian Ratna Sawitri (Faculty of Psychology, Diponegoro University, 2025)
Perceived employability among university students is the driving force behind their confidence in entering the job market, shaping how they view their skills, academic achievements, and future career potential. This study seeks to explore and analyze the research trend of perceived employability among university student in one decade. Using literature review with a bibliometric approach and SCOPUS database for this study and used university student perceived employability as the main keyword. The analysis was conducted using VOSviewer and Microsoft Excel. The bibliometric analysis included document type, authorship, institution, subject area, growth trend, and future research directions. The result shows 5 clusters explained that perceived employability among university student is discussed in various fields such as core elements during university, internal factors, outcomes, perception, and entrepreneurship. For future research, it is expected that researchers can discuss perceived employability related to the topics mentioned in the discussion section.